The Ethics of Artificial Intelligence (AI) Utilization in Qur'anic Studies: An Islamic Philosophical Perspective - Zuhri, M. Tajudin; Sahlani, Lalan; Munawaroh, Nenden (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2024)
Artificial Intelligence (AI) has presented a major breakthrough in Qur'anic studies, enabling text analysis, thematic classification, and the development of digital commentaries. These innovations provide opportunities to expand accessibility and improve the accuracy of Qur'anic analysis. However, AI also poses ethical challenges, including the potential for algorithmic bias, distortion of meaning, and threats to Islamic scholarly authority. From an Islamic perspective, these challenges require a clear ethical framework so that the utilization of AI does not conflict with Qur'anic values.             This research aims to identify Islamic ethical principles relevant to the use of AI in Qur'anic studies and develop a philosophical framework based on maqashid sharia. The methodology used is library research with a content analysis approach to classical and modern Islamic literature on ethics, Islamic philosophy, and maqashid sharia. The results show that principles such as justice (al-'adl wa al-ihsan), expediency (maslahah), and prudence (wara') should be the main guides in any application of AI in the Qur'anic context. In addition, maqashid sharia provides an evaluation framework to ensure that AI applications support the main objectives of sharia, such as safeguarding religion (hifdh ad-din) and reason (hifdh al-'aql).             The conclusion of this study confirms that the ethical use of AI in Qur'anic studies requires an integration of technological innovation and Qur'anic values. With the application of strong Islamic ethical principles, AI can be effectively used to support Qur'anic understanding, without compromising the integrity of the text and scholarly authority. This study offers a contribution to the development of comprehensive ethical guidelines to bridge technological advancement with the spiritual and scholarly needs of Muslims. Keyword: Artificial Intelligence (AI), Qur'anic Studies, Philosophical Islam   Etika Pemanfaatan Artificial Intelligence (AI) dalam Studi Al-Qur'an: Perspektif Filosofis Islam Abstrak Artificial Intelligence (AI) telah menghadirkan terobosan besar dalam studi Al-Qur'an, memungkinkan analisis teks, klasifikasi tematik, hingga pengembangan tafsir digital. Inovasi ini memberikan peluang untuk memperluas aksesibilitas dan meningkatkan akurasi analisis Qur'ani. Namun, kehadiran AI juga memunculkan tantangan etis, termasuk potensi bias algoritma, distorsi makna, hingga ancaman terhadap otoritas keilmuan Islam. Dari perspektif Islam, tantangan ini memerlukan kerangka etika yang jelas agar pemanfaatan AI tidak bertentangan dengan nilai-nilai Qur'ani. Penelitian ini bertujuan untuk mengidentifikasi prinsip-prinsip etika Islam yang relevan dengan penggunaan AI dalam studi Al-Qur'an serta mengembangkan kerangka filosofis berbasis maqashid syariah. Metodologi yang digunakan adalah penelitian kepustakaan (library research) dengan pendekatan analisis konten terhadap literatur Islam klasik dan modern tentang etika, filsafat Islam, dan maqashid syariah. Hasil penelitian menunjukkan bahwa prinsip-prinsip seperti keadilan (al-‘adl wa al-ihsan), kemanfaatan (maslahah), dan kehati-hatian (wara') harus menjadi panduan utama dalam setiap penerapan AI dalam konteks Qur'ani. Selain itu, maqashid syariah memberikan kerangka evaluasi untuk memastikan bahwa aplikasi AI mendukung tujuan utama syariah, seperti menjaga agama (hifdh ad-din) dan akal (hifdh al-‘aql). Kesimpulan penelitian ini menegaskan bahwa etika pemanfaatan AI dalam studi Al-Qur'an memerlukan keterpaduan antara inovasi teknologi dan nilai-nilai Qur'ani. Dengan penerapan prinsip etika Islam yang kuat, AI dapat digunakan secara efektif untuk mendukung pemahaman Al-Qur'an, tanpa mengorbankan integritas teks dan otoritas keilmuan. Studi ini menawarkan kontribusi bagi pengembangan panduan etika yang komprehensif untuk menjembatani kemajuan teknologi dengan kebutuhan spiritual dan keilmuan umat Islam. Keyword : Artificial Intelligence (AI), Studi Al-Qur'an, Filosofis Islam